Hyaluronan and Layilin Mediate Loss of Airway Epithelial Barrier Function Induced by Cigarette Smoke by Decreasing E-cadherin - Forteza, Rosanna Malbran (American Society for Biochemistry and Molecular Biology, 2012)
Cigarette smoke (CigS) exposure is associated with increased bronchial epithelial permeability and impaired barrier function. Primary cultures of normal human bronchial epithelial cells exposed to CigS exhibit decreased E-cadherin expression and reduced transepithelial electrical resistance. These effects were mediated by hyaluronan (HA) because inhibition of its synthesis with 4-methylumbelliferone prevented these effects, and exposure to HA fragments of <70 kDa mimicked these effects. We show that the HA receptor layilin is expressed apically in human airway epithelium and that cells infected with lentivirus expressing layilin siRNAs were protected against increased permeability triggered by both CigS and HA. We identified RhoA/Rho-associated protein kinase (ROCK) as the signaling effectors downstream layilin. We conclude that HA fragments generated by CigS bind to layilin and signal through Rho/ROCK to inhibit the E-cadherin gene and protein expression, leading to a loss of epithelial cell-cell contact. These studies suggest that HA functions as a master switch protecting or disrupting the epithelial barrier in its high versus low molecular weight form and that its depolymerization is a first and necessary step triggering the inflammatory response to CigS.